Implementation of Family Hope Program (Program Keluarga Harapan) in Bojong Village: Ministerial Regulation Study - Farhani Mubarok, Husni; Heri, Heri; Ridwan Caesar, Muhammad; Nugraha, Ari (VARIA HUKUM, 2025)
Abstract: The Family Hope Program (PKH) is a social protection program that provides cash assistance to low-income families who are designated as Beneficiary Families (KPM). PKH is a program targeting low-income families, with the primary focus on economically disadvantaged families. PKH is an initiative focused on the development and enhancement of human resources, with a particular emphasis on aspects of education, health, and social welfare. The purpose of this study was to determine the Implementation of the Family Hope Program Policy in Bojong Village, to find out the factors that hindered the Implementation of the Family Hope Program Policy in Bojong Village, to find out the efforts being made to overcome obstacles to the Implementation of the Family Hope Program Policy in Bojong Village—the third stage of payment and finally the commitment verification. The driving and inhibiting factors for PKH, which were implemented in Bojong Village, Bungbulang District, were that, although not fully implemented, the community acknowledged that this program had helped and provided relief to the community.